Cholangioscopy using a new type of cholangioscope for the diagnosis of biliary tract disease: a case series - Cennamo, V.; Luigiano, C.; Fabbri, C.; Maimone, A.; Bazzoli, F.; Ceroni, L.; Morace, C.; Jovine, E. (Endoscopy, 2012)
We present an initial report regarding the clinical usefulness of peroral cholangioscopy, using a new type of cholangioscope, the Polyscope. Peroral cholangioscopy was performed in four patients with strictures after orthotopic liver transplantation (OLT) which were suspected of being ischemic biliary lesions, in three with indeterminate biliary strictures, in three with suspected retained bile duct stones, and in two for evaluation of the intraductal spread of adenomatous tissue after an ampullectomy. In all cases peroral cholangioscopy was performed successfully without complications. On the basis of direct viewing and/or tissue sampling a correct diagnosis was reached in all cases: in all patients who underwent OLT the strictures were not ischemic; the indeterminate strictures were all benign; and, in patients with suspected stones, complete clearance was confirmed. Intraductal spread was confirmed in one patient and excluded in the other. In our experience, peroral cholangioscopy using a Polyscope is a safe and effective method for diagnosing bile duct lesions.